Analysis of microbiome in gastrointestinal stromal tumors: Looking for different players in tumorigenesis and novel therapeutic options. Issue 8 (21st June 2022) - Ravegnini, Gloria; Fosso, Bruno; Ricci, Riccardo; Gorini, Francesca; Turroni, Silvia; Serrano, Cesar; Pilco‐Janeta, Daniel F.; Zhang, Qianqian; Zanotti, Federica; De Robertis, Mariangela; Nannini, Margherita; Pantaleo, Maria Abbondanza; et al.
Abstract: Preclinical forms of gastrointestinal stromal tumor (GIST), small asymptomatic lesions, called microGIST, are detected in approximately 30% of the general population. Gastrointestinal stromal tumor driver mutation can be already detected in microGISTs, even if they do not progress into malignant cancer; these mutations are necessary, but insufficient events to foster tumor progression. Here we profiled the tissue microbiota of 60 gastrointestinal specimens in three different patient cohorts—micro, low‐risk, and high‐risk or metastatic GIST—exploring the compositional structure, predicted function, and microbial networks, with the aim of providing a complete overview of microbial ecology in GIST and its preclinical form. Comparing microGISTs and GISTs, both weighted and unweighted UniFrac and Bray–Curtis dissimilarities showed significant community‐level separation between them and a pronounced difference in Proteobacteria, Firmicutes, and Bacteroidota was observed. Through the LEfSe tool, potential microbial biomarkers associated with a specific type of lesion were identified. In particular, GIST samples were significantly enriched in the phylum Proteobacteria compared to microGISTs. Several pathways involved in sugar metabolism were also highlighted in GISTs; this was expected as cancer usually displays high aerobic glycolysis in place of oxidative phosphorylation and rise of glucose flux to promote anabolic request. Our results highlight that specific differences do exist in the tissue microbiome community between GIST and benign lesions and that microbiome restructuration can drive the carcinogenesis process. Abstract : This is the first work analyzing microbiome community in GIST and microGIST looking for novel players in GIST tumorigenesis. Our results highlight that specific differences do exist in the microbiome community between GISTs and benign lesions and that microbiome restructuration can happens and may drive the carcinogenesis process. Beside molecular alterations taking place over GIST evolution to malignant lesions, a key under‐considered factor can be represented by tumor microenvironment (i.e., microbiome) and further studies should deepen its role. The figure was partially created with Biorender.com.